Progress in bacterial cellulose matrices for biotechnological applications. (August 2016) - Cacicedo, Maximiliano L.; Castro, M. Cristina; Servetas, Ioannis; Bosnea, Loulouda; Boura, Konstantina; Tsafrakidou, Panagiota; Dima, Agapi; Terpou, Antonia; Koutinas, Athanasios; Castro, Guillermo R.
Graphical abstract: Highlights: Cellulose producing microorganisms: the Komagataeibacter genus and main characteristics. Cultivation and media to produce bacterial cellulose. Modification of bacterial cellulose: in-situ and ex -situ techniques. Bacterial cellulose in biotechnological processes: enzyme and cell immobilization. Multilayer bioreactors based on bacterial cellulose matrices. Abstract: Bacterial cellulose (BC) is an extracellular polymer produced by many microorganisms. The Komagataeibacter genus is the best producer using semi-synthetic media and agricultural wastes. The main advantages of BC are the nanoporous structure, high water content and free hydroxyl groups. Modification of BC can be made by two strategies: in-situ, during the BC production, and ex-situ after BC purification. In bioprocesses, multilayer BC nanocomposites can contain biocatalysts designed to be suitable for outside to inside cell activities. These nanocomposites biocatalysts can (i) increase productivity in bioreactors and bioprocessing, (ii) provide cell activities does not possess without DNA cloning and (iii) provide novel nano-carriers for cell inside activity and bioprocessing. In nanomedicine, BC matrices containing therapeutic molecules can be used for pathologies like skin burns, and implantable therapeutic devices. In nanoelectronics, semiconductors BC-based using salts and synthetic polymers brings novel films showing excellent optical and photochemical properties.